(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article examines the trends of attracting green direct investments to the world economy. It is also given as an example of the countries attracting the most active green investment to the world economy. During 2013-2023, foreign direct investments attracted to the economies of the world countries and the volume of green investments made in developing markets by region were analyzed.